Designing Experiments for a Research-Oriented Model of Learning in the Subject of Technique in Lower Secondary Education - ĎURIŠ, MILAN; OČKAJOVÁ, ALENA; KVASNOVÁ, PETRA (Journal of Education, Technology and Computer Science, 2023)
In this article, attention is paid to the selected design of experiments that will be part of a research-oriented model of students’ education in the subject of Technique in lower secondary education in the Slovak Republic. The proposed model of education reflects the long-term needs of students’ education in the subject of Technique, which, despite the updated content of the curriculum in the Educational Standard of the subject of Technique, have not yet been met. Part of the model is the application of formative assessment of students in the framework of the implemented experiential learning of students. Due to the limited scope of this article, two experiments from the set of proposed experiments are presented with the methodology of the actual implementation. The given problem is solved within the KEGA project No. 006UMB-4/2022 in the years 2022–2024.